A Study of the Regiochemistry in the Synthesis of Pyrano[3,4-c]pyridines - Sirakanyan, Samvel N.; Spinelli, Domenico; Kartsev, Victor A.; Geronikaki, Athina; Hakobyan, Elmira K.; Ayvazyan, Armen G.; Tamazyan, Rafael A.; Hovakimyan, Anush A. (Current Organic Chemistry, 2021)
Aims: Biological studies have shown that some condensed derivatives of pyrano[3,4- c]pyridines 6 exhibited pronounced biological activity. Considering these results, the principal aim of this work is to study the regiochemistry of the synthesis of pyrano[3,4-c]pyridines 6, to optimize the reaction conditions and thus to increase the previously observed low yields of pyrano[ 3,4-c]pyridines. Background: Within this research line, some of us, several years ago, developed a method for the preparation of 6-oxopyrano[3,4-c]pyridines 6 starting from 2,2-dimethyltetrahydro-4Hpyran- 4-one 1. In these studies, we separated and identified only the most expected reaction products 6-oxopyrano[3,4-c]pyridines 6. On the basis of this datum, we suggested that the enamines 2 and 3, reacting with acyl chlorides, were not acylated at C-3 and that 5-acylpyran-4- ones 4 were the only products of the reaction. We have justified this result by considering the steric effects exerted by the two methyl groups present in the pyran ring. Moreover, we did not identify the products at the second reaction center: that is, the isomeric compounds 7 and this result was justified considering the different reactivity of aliphatic and cyclic ketone groups. Objectives: The main objectives of this work were: • implementation of the reaction of 2,2-dimethyltetrahydro-4H-pyran-4-one 1 with morpholine; • acylation of the obtained enamines 2 and 3 with acyl chlorides under Stork conditions; • synthesis of pyranopyridines 6-8 based on β-diketones: 3-acylpyran-4-ones 4 and 5-acylpyran-4-ones 5; • confirmation of the structure of the obtained compounds. Methods: For the synthesis of pyrano[3,4-c]pyridines known methods were used. Thus, the reaction of starting 2,2- dimethyltetrahydro-4H-pyran-4-one 1 with morpholine in benzene led to the formation of isomeric enamines 2 and 3. After, they were acylated with acyl chlorides under Stork conditions with formation of two β -diketones: 3- acylpyran-4-ones 4 and 5-acylpyran-4-ones 5. Finally, in order to obtain the aimed pyrano[3,4-c]pyridines 6, the obtained β-dicarbonyl compounds 4 and 5 (as a mixture of isomers) were reacted with 2-cyanoacetamide in ethanol in the presence of diethylamine, according to the Knoevenagel condensation. The structure of the obtained compounds has been unambiguously confirmed by using a wide spectrum of physico-chemical methods (NMR, IR, Xray structural and elemental analysis) and, in the instance of compounds 7, also by an alternative synthesis. Results: Starting from the 2,2-dimethyltetrahydro-4H-pyran-4-one 1 a series of new and already known 6- oxopyrano[3,4-c]pyridines 6 were synthesized. As a result of the study of the regiochemistry in the synthesis of pyrano[3,4-c]pyridines, of the four possible isomer pyranopyridines 6-9, we have succeeded in identifying three of them (6-8). Thus, isomer pyranopyridines 7 and 8 were identified in the mixture with the main compounds 6. Moreover, isomeric pyrano[3,4-c]pyridines 8 were detected when alkyl groups are present in the starting compounds 4 and 5, while isomeric pyrano[4,3-b]pyridines 7 were detected in the case of the presence of aromatic groups. Unfortunately, we have not been able to isolate compounds 7 and 8 in the pure state from the reaction mixtures. At now, we have not been able to detect and identify isomeric pyrano[4,3-b]pyridines 9. On the whole, we have been able to better the effectiveness of the synthesis of pyrano[3,4-c]pyridines 6, increasing their yields by ≈ 5-15%. Conclusion: As a result of our investigation, we have found that the acylation reaction of enamines 2 and 3 and the cyclization reaction of β-diketones 4 and 5 are not regioselective. Therefore, we can state that enamines 2 and 3 can be acylated at both C-3 and C-5 with the formation of a mixture of 3-acylpyran-4-ones 4 and of 5-acylpyran-4-ones 5. Their condensation with 2-cyanoacetamide led to the formation of mixtures of regioisomeric pyranopyridines 6- 8. In conclusion, as a result of our present research, we can say that we have been able to increase the effectiveness of the synthesis of pyranopyridines, largely improving our previous results. Other: Now, we are working to look for the fourth isomeric pyrano[4,3-b]pyridines 9 by using the most modern and fine methods. Moreover, we hope that we shall be able to separate the mixtures of pyranopyridines 6-8: any way they can be used for further syntheses as they are.
Keywords: Pyranopyridines